Training on Diversifying Local Food Tortillas of Glutinous Corn - Sri Mardiyati; Mohammad Natsir; Muh. Arifin Fattah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Glutinous corn is one of the local foods that are hereditary consumed by most people in the province of South Sulawesi. The diversification of glutinous corn-based processed foods in the region is still mostly boiled corn, bassang, and marning corn. The diversification of processed local food requires high creativity to meet the changing demand for consumer tastes, and to increase the added value of products. Specific goals and targets of this community service activity include: (1) increase the knowledge of housewives towards diversification of local food processed glutinous corn and entrepreneurial insights, (2) improve skills about processing local glutinous corn into multi-flavored glutinous corn tortillas, and (3) create processed corn tortilla products. Sticky rice is a variety of flavors that are hygienic and have attractive packaging and brands. To achieve the expected external goals and targets, the implementation methods used in this activity are extension and training methods. The results of the implementation of this devotional activity include: (1) The implementation of this community service program can run well (partners respond positively); (2) This program is beneficial especially for housewives to increase household income; (3) This program in general has been able to improve the knowledge and skills of housewives about entrepreneurship insights, diversification of local glutinous corn processed food, processing techniques, packaging, labelling, and good branding; (4) Housewives are mostly interested and interested in developing local food diversification businesses processed glutinous corn in the form of tortillas, both independently and in groups because of the availability of abundant local raw materials and relatively easy to do.